Deep learning based predictive analytics for decentralized content caching in hierarchical edge networks - Chakraborty, Dhruba; Rabbi, Mahima; Hossain, Maisha; Khaled, Saraf Noor; Oishi, Maria Khanom (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.